Enhanced electric power transmission by hybrid compensation technique - Palanichamy, Chinnasamy; Kiu, G. (2015)
In today's competitive environment, new power system engineers are likely to contribute immediately to the task, without years of seasoning via on-the-job training, mentoring, and rotation assignments. At the same time it is becoming obligatory to train power system engineering graduates for an increasingly quality-minded corporate environment. In order to achieve this, there is a need to make available better-quality tools for educating and training power system engineering students and in-service system engineers too. As a result of the swift advances in computer hardware and software, many windows-based computer software packages were developed for the purpose of educating and training. In line with those packages, a simulation package called Hybrid Series-Shunt Compensators (HSSC) has been developed and presented in this paper for educational purposes.